A Fortnite and odd days: the console wars - Alba Ribera Martínez (Market and Competition Law Review)
The videogames industry is called to play a key role in the development and design of the future digital arena, ranging from the up-and-coming metaverse to the digital platforms’ future innovation. At this point, projections show that video gaming can surpass $220 billion in revenue in 2024, whereas the entertainment industry’s revenues are rapidly decreasing. Still, the video gaming sector has gone largely unnoticed by competition law authorities. A few skewed and inconsistent decisions have tried to set out the relevant product and geographical markets. However, the subsequent developments over the years do not show a linear sequence of events. Instead, several breakthroughs such as introducing cloud gaming and subscription video gaming services have contributed to blurring the lines of market delineation altogether. The European Commission’s approach through merger control has been instrumental to provide some guidance on the subject, although its Vivendi/Activision, Activision Blizzard/King and Microsoft/ZeniMax have not paid attention to the special characteristics of video gaming, namely differences between user experience when playing different game genres and when playing across platforms. Given the foregoing, we will first address the videogame market’s economic conditions and particularities overlooked by competition authorities when performing their analysis, namely in the preliminary stage of market definition. Based on these findings, the article builds on the calls for intervention with regard to the Microsoft/Activision Blizzard4 operation and instrumentalises it as a yardstick to measure the wider impact of acquisitions within the video gaming market.